Review of the ethnobotany, phytochemistry, pharmacology, and toxicity studies of the genus Adenia - Mouafon, Iliassou L.; Katerere, David R. (Frontiers in Pharmacology, 2025)
BackgroundThe genus Adenia has a rich history of traditional medicinal use across various cultures, particularly in Africa and parts of Asia. The present review summarizes key features of the genus Adenia, focusing on its occurrence, distribution, isolation, bioactivities, and toxicities.Material and methodsA thorough literature review was conducted using databases such as Google Scholar, PubMed, ScienceDirect, JSTOR, and Web of Science. The search utilized the keyword “Adenia” in combination with relevant terms like “distribution,” “traditional use,” “phytochemicals,” “chemical compounds,” “pharmacology,” “bioactivity,” and “toxicity.”ResultsOur search yielded 3,724 records, with 88 studies from 1935 to 2024 meeting our criteria. The findings indicate that the genus Adenia comprises over 106 species of climbing plants, commonly found in tropical and subtropical regions. In traditional medicine, several Adenia species have been employed in various cultures for medicinal purposes, treating ailments such as wounds, leprosy, malaria, infections, infertility, colic, dysentery, hypertension, rheumatism, headaches, abdominal pain, and cancer. Chemical investigations have identified 27 secondary metabolites including alkaloids, glycosides, flavonoids, and ribosome-inactivating proteins (RIPs), particularly type 2, which are associated with cytotoxic and toxic effects. Pharmacological studies of chemical constituents and extracts from Adenia species have revealed a broad spectrum of biological activities, including cytotoxicity, antimicrobial, antioxidant, anti-inflammatory, analgesic, anticholinesterase, neuropharmacological, antidepressant, antihyperglycaemic, anti-anemic, anticoagulant, antithrombotic, thrombolytic, and anesthetic activities. Despite their therapeutic benefits, concerns regarding safety and toxicity are significant, necessitating comprehensive evaluations and standardized methodologies for assessing their efficacy. Thus, future research should focus on validating the traditional uses of Adenia species through rigorous scientific methods to ensure their safety and efficacy in modern medicine.